Mengembangkan kreativitas dan karakter bangsa melalui Kurikulum Merdeka di Madrasah - Muliardi, Muliardi (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2023)
This study discusses the Kurikulum Merdeka as a solution to developing students' creativity and national character. This study uses a descriptive-analytic approach by reviewing various literature and data sources to understand the influence of the Kurikulum Merdeka. The findings reveal that the Kurikulum Merdeka helps develop critical, creative, and innovative thinking skills and a national character in Madrasah. Students can freely explore their interests and talents by using a student-centred approach. This study will contribute to education development in Madrasah and provide teachers and policymakers with a reference for developing curricula that foster students' creativity and national character.